2007
DOI: 10.1007/s00595-006-3353-z
|View full text |Cite
|
Sign up to set email alerts
|

A Shorter Skin Incision Technique for the Repair of Infrarenal Abdominal Aortic Aneurysms

Abstract: We define minimally invasive vascular surgery as surgery performed with a small abdominal skin incision that does not expose the intestine to air while providing a good operative field that does not place any undue stress on the surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Some studies have shown that the time to first flatus is 2-3 PODs and the time to resuming a diet is 4-8 PODs following transperitoneal abdominal aortic surgery [6,9,10,17]. Similar to previous reports, the number of days to first flatus and to resuming food intake was 2.35 and 3.86 days, respectively, in our control group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some studies have shown that the time to first flatus is 2-3 PODs and the time to resuming a diet is 4-8 PODs following transperitoneal abdominal aortic surgery [6,9,10,17]. Similar to previous reports, the number of days to first flatus and to resuming food intake was 2.35 and 3.86 days, respectively, in our control group.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, reports indicate that early oral intake does not reduce the duration of postoperative ileus or increase the rate of nasogastric tube reinsertion significantly [6]. Minimally invasive surgery, such as minilaparotomy, laparoscopic procedures, and endovascular surgery, may lead to earlier recovery of postoperative bowel function and shorter hospital stays, because of reduced tissue trauma [7][8][9][10][11]. However, minimally invasive techniques are not available for all surgical procedures and we must devise new surgical techniques to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…22,25,26 The MINI patients did not need a significant increase in fluid recovery because of less intestinal edema and earlier return to oral intake. 22,25,26 The MINI patients did not need a significant increase in fluid recovery because of less intestinal edema and earlier return to oral intake.…”
Section: Discussionmentioning
confidence: 98%
“…The length of the abdominal skin incision for abdominal aortic aneurysm repair has been determined to impact on the presence of ileus and time to return to normal diet. Hiromatsu and colleagues established that those patients with a skin incision of less than 15cm had a significantly smaller incidence of ileus when compared to a group of patients that had a skin incision of greater than 20cm (Hiromatsu et al, 2007). Laparoscopic repair has also demonstrated a shorter period of ileus and a quicker return to diet when compared to open repair (Coggia et al, 2005).…”
Section: Risk Factorsmentioning
confidence: 99%